The effect of sowing dates on the yield of soybean (Glycine max (L.) Merr.) accessions differing in maturity schedules under the climate conditions of Irkutsk Province - N. B. Katysheva; A. V. Pomortsev; N. V. Dorofeev; S. Yu. Zorina; L. G. Sokolova; A. S. Zhuravkova; Yu. S. Bukin; A. I. Katyshev (Труды по прикладной ботанике, генетике и селекции)
Background. Soybean is the main supplier of complete vegetable protein and oil. Prior to the emergence of new early-ripening cultivars, this crop was not cultivated in Irkutsk Province. Its introduction into the area requires a detailed study of agricultural practices, primarily the choice of optimal sowing dates. Materials and methods. Soybean cv. ‘Barguzin’, late-ripening under the conditions of Irkutsk Province, and early-ripening accession 15 served as the research objects. Field studies were carried out in 2019–2021. There were four sowing dates, from the first ten-day period of May through the first ten-day period of June. Results and conclusion. Cv. ‘Barguzin’ appeared highly productive under the climate of Irkutsk Province (its average seed yield in 2019–2021 was 2.7 t/ha), but its productivity was significantly influenced by weather conditions and sowing dates (seed yields varied from 1.4 to 3.6 t/ha). The optimal sowing times for this cultivar are the first and second ten-day periods of May. Early-ripening accession 15 was characterized by more stable yield values in the studied years (average productivity was 2.4 t/ha, minimum 1.9 t/ha, and maximum 3.2 t/ha). The preferred sowing times for this accession are the second and third ten-day periods of May. The case study of two soybean genotypes differing in maturation schedules revealed the need for individual selection of sowing dates. It was shown that the early-ripening soybean genotype imposed less stringent requirements on the choice of sowing dates.